2020
DOI: 10.4012/dmj.2019-020
|View full text |Cite
|
Sign up to set email alerts
|

Monomer conversion, dimensional stability, biaxial flexural strength, and fluoride release of resin-based restorative material containing alkaline fillers

Abstract: The aim of this study was to assess monomer conversion, dimensional stability (mass and volume changes), biaxial flexural strength (BFS), and fluoride release of recently developed resin composites containing alkaline fillers (Cention N; CN) compared with resinmodified glass ionomer cements (RMGICs: Riva LC; RL and Fuji II LC; FL), and conventional composite (Z350). FL showed highest monomer conversion (88±2%) followed by RL (73±10%), CN (59±2%), and Z350 (50±2%). RL exhibited highest mass and volume increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 47 publications
7
33
0
Order By: Relevance
“…It has been demonstrated that powder/liquid (P/L) ratio of a resin-based cement affects its viscosity. Higher P/L ratio leads to higher viscosity 20 .…”
Section: Discussionmentioning
confidence: 98%
“…It has been demonstrated that powder/liquid (P/L) ratio of a resin-based cement affects its viscosity. Higher P/L ratio leads to higher viscosity 20 .…”
Section: Discussionmentioning
confidence: 98%
“…Phosphate ions play a role in formation and deposition of hydroxyapatite on the tooth surface and structures adjacent to a restoration. They also have a prominent role in the process of remineralization [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, increased ion release over time leads to degradation and compromises the mechanical properties of the material. Moreover, the buffering effect of RMGI is also reinforced by the leaching of aluminum ions into the acidic environment and can also play a role in pH rise following acidification [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…For the chemical activated polymerization, the composites were left cured on the ATR diamond for 10 min. Degree of monomer conversion (MC) of the composites was calculated using the following equation 22) .…”
Section: Monomer Conversionmentioning
confidence: 99%